Novel thiazolyl-pyrimidine derivatives as potential anticancer agents: Synthesis, biological evaluation, and molecular docking studies - Tariq Z. Abolibda; Abdel-Aziz A.A. El-Sayed; Basant Farag; Magdi E.A. Zaki; Abdulwahed Alrehaily; Hossein M. Elbadawy; Ahmad A. Al-Shahri; Saleh R. Alsenani; Sobhi M. Gomha (Results in Chemistry)
We synthesized and spectroscopically confirmed a series of 1,3-thiazolyl-pyrimidine derivatives to investigate their potential role in cancer therapy. These were created by reacting 2-(1-(6-methyl-2-oxo-4-phenyl- 1,2,3,4-tetrahydropyrimidin-5-yl)ethylidene)hydrazine-1-carbothioamide with hydrazonoyl halides and α-halo compounds, with structures confirmed by spectroscopy. The growth-inhibitory potential of these compounds against HepG2 liver cancer cells was assessed using the MTT assay. Five compounds, namely 8a, 10, 12a, 12b, and 14, exhibited promising anticancer activity with IC50 values of 5.02 ± 1.83, 4.04 ± 1.37, 3.81 ± 1.96, 2.39 ± 0.75, and 3.27 ± 1.13 μM, respectively, all of which were more effective than doxorubicin (IC50 = 6.18 ± 0.29 μM). Molecular docking analyses were conducted to investigate the probable binding conformations of the most potent anticancer agents. The docking studies were in good agreement with the in vitro biological results, revealing that compounds 12b, 14, 12a, 10, and 8a demonstrated strong molecular interactions with protein CK2 α. The compounds may serve as adjuvants in cancer treatment. In silico ADMET studies revealed that the synthesized compounds exhibit favorable oral bioavailability profiles.